Dietary calcium intake in postmenopausal Malaysian women: comparison between the food frequency questionnaire and three-day food records - Chee, WSS; Suriah, AR; Zaitun, Y; Chan, SP; Yap, SL; Chan, YM (Wiley, 2002)
The objective of this study was to compare the dietary calcium intakes assessed by a quantitative food frequency questionnaire (FFQ) and the three-day food record method in 230 Chinese postmenopausal women aged 50–65 years in Kuala Lumpur. The results showed that the mean calcium intake from the dietary records was 447 ± 168 mg/day and 499 ± 211 mg/day from the FFQ. The mean difference in intake by the two methods was 51.3 mg (95% CI = – 30.8 – 77.9; SD = 181.2, P > 0.05), which did not differ significantly from zero. Pearson’s correlation coefficient of 0.56 was obtained between the two methods. Ninety-five percent of the individuals classified by food records fell into the same or within-one-quartile category when classified by FFQ. Forty-eight percent were classified into the same quartile by both methods. No subjects were grossly misclassified by the FFQ. The FFQ correctly identified subjects with calcium intakes below the Malaysian recommended daily allowance (450 mg/day) with 60% specificity and with 92% specificity for women consuming less than 800 mg calcium/day. In conclusion, the FFQ developed was a useful, rapid clinical tool for assessing calcium intake and identifying postmenopausal Chinese women with low calcium intakes in Malaysia.